Taxpayer Perception and Income Tax Filing Compliance among Small Taxpayers in Mbarara City - Kijjambu, Frederick Nsambu; Mwesigye, Boaz (American Journal of Finance, 2024)
Purpose: This study is about establishing the relationship between taxpayer perception and income tax filing compliance among small taxpayers in Mbarara city. The study is driven by the fact that despite Uganda Revenue Authority’s efforts to improve tax compliance, income tax filing compliance is still low among small taxpayers in Uganda in general and Mbarara city in particular. Materials and Methods: A cross-sectional study design was used to collect data from 33,979 small taxpayers in Mbarara city out of which 31,324 were individual taxpayers while 2,655 were nonindividual taxpayers. The sample size included 380 respondents out of which 350 were individual taxpayers while 30 were non-individual taxpayers. Systematic random sampling was used to select respondents from each of the six divisions of Mbarara city. A questionnaire method was employed in data collection where self-administered 5-point Likert type questionnaire with a Content Validity Index (CVI) of .91 and a Cronbach’s alpha (α) of .86 was used in data collection. Data was analyzed using SPSS version 26.0 where correlation coefficients were generated and presented in a table. Findings: Results from the correlation analysis revealed that taxpayer perception was positively and significantly related to income tax filing compliance (r=.715**, p<0.05). The study concludes that efforts aimed at improving taxpayer perceptions play a significant role in improving income tax filing compliance. Implications to Theory, Practice and Policy: The study recommends a need for the government and tax authorities, in this case, Uganda Revenue Authority to put in place strategies and programs aimed at changing individual perceptions, social understanding and personal motivations regarding income tax filing. Some of these strategies include intensifying tax education and outreach services of the mobile tax office ‘Tujenge Bus Services’ to all locations; introducing basic tax education at earlier stages of formal education such that citizens are informed about their future obligations to file income tax returns; translating all information about income tax filing in different local languages and publishing the same in print format for public access at no cost; and recruiting more tax agents within Mbarara city who can assist small taxpayers in income tax filing at a reasonable fee. The assumptions of the Motivational Posturing Theory could also be relevant in assisting the tax authorities to change the personal and societal perceptions about income tax filing and motivate them to willingly comply with their filing obligations. The study has significant implications for policy making as it identifies a need for government and tax authorities to establish policies and offer incentives and motivational postures that prioritize voluntary compliance rather than introducing sanctions to enforce income tax filing compliance.
Keywords: Taxpayer Perception; Income Tax Filing Compliance; Small Taxpayer